If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(-1c + (-12)) = -2c + (-12) -2(-1c + -12) = -2c + (-12) Reorder the terms: -2(-12 + -1c) = -2c + (-12) (-12 * -2 + -1c * -2) = -2c + (-12) (24 + 2c) = -2c + (-12) 24 + 2c = -2c + -12 Reorder the terms: 24 + 2c = -12 + -2c Solving 24 + 2c = -12 + -2c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '2c' to each side of the equation. 24 + 2c + 2c = -12 + -2c + 2c Combine like terms: 2c + 2c = 4c 24 + 4c = -12 + -2c + 2c Combine like terms: -2c + 2c = 0 24 + 4c = -12 + 0 24 + 4c = -12 Add '-24' to each side of the equation. 24 + -24 + 4c = -12 + -24 Combine like terms: 24 + -24 = 0 0 + 4c = -12 + -24 4c = -12 + -24 Combine like terms: -12 + -24 = -36 4c = -36 Divide each side by '4'. c = -9 Simplifying c = -9
| 3[a+1]=19-5a | | -15t=-33-5t | | -15=-33-5t | | 4+x/-5=19 | | 4r+8-4=16 | | 7a=a-24 | | 7a=a-33-5t | | 3(3x-5)=39 | | 5(x+1)+10=5x+10x+1+9 | | 5(x+1)+10=5x+10+1+9 | | 5(x+1)+10=5+10+1+9 | | (7/8)/(5/18) | | 3x-9=44-2x | | 6x+2ab=7x-3ab | | ((-4)^2)+3*2/-9+4 | | c^2-3c-54=0 | | -4(6k+8)=88 | | n+(-6)=-11 | | 12rs-6s-5s= | | (-4)^2+3*2/-9+4 | | 3a+1=(-3.6)(a+(-1)) | | 4/x=(9/8)*x+1 | | 15=n+(-2) | | 2w=xyz | | 5x+9=6x+10 | | z/2+11=31 | | 5x+4=4x+1 | | -5v=-50 | | 13.25=.06x | | 5/x-4=6/x-3 | | n-(-2)=-3 | | 2=x-(-16) |